Fearsome Horses: the nightmares that wrecked Lambton Quay - Humphris, Adrian; Mew, Geoff (Architectural History Aotearoa, 2022)
The 1970s saw an unprecedented wave of building demolition along the western side of Lambton Quay as well as in other parts of central Wellington. A 1972 survey carried out by the City Corporation identified buildings they determined to be at risk of collapse in a moderate earthquake, with "A" being the highest risk category. Those classified as "A" were then targeted for demolition. The survey followed a Chamber of Commerce discussion paper produced in November 1971 that was concerned with future regional development. As a result, many small buildings were replaced with fewer, much larger tower blocks. These tower blocks were built to maximise returns on investment according to the size of the footprint (with little or no regard for aesthetics). Although some were completed in the 1970s, others were not topped off until the 1980s. This paper evaluates the reasons for the apparent sudden upsurge in awareness of "awesome forces," the publicity given to the survey, and the likely outcomes for building owners. It traces the building history of a varied selection of "at risk" commercial premises; a few of which have survived - at least partially in façade form - and some of the buildings that succeeded them. At the time there seems to have been little historical consideration or awareness of what was being lost, and strengthening options were seldom explored in depth. Hence many varied two- to five-storey buildings erected in late Victorian and early Edwardian times were irreversibly pulled down to be replaced by characterless, anonymous and overbearing tower blocks.